Upacara Ngerebeg Di Pura Kahyangan Kedaton Desa Kukuh, Kecamatan Marga, Kabupaten Tabanan - Ni Wayan Yusi Armini; I Nyoman Darsana (Sphatika: Jurnal Teologi, 2021)
From the results of this study, it can be seen that the Ngerebeg ceremony is a Dewa Yadnya ceremony carried out by the people of Kukuh Village, as a ritual that aims to neutralize negative human traits (sad ripu), the Ngerebeg ceremony is held at the Kahyangan Kedaton temple where Ida Bhatara's meditation is in the form of Barong Ket and Barong Landung tedun surround the temple area. All village stakeholders prepare water to be sprinkled on to the community and women and girls prepare tetabuhan facilities such as palm wine, wine, beer for offerings to Bhuta Kala. The purpose of this study is that researchers want to provide a clear understanding of the Ngerebeg ceremony. The results of this study are useful for researchers and for the Hindu community to know more about the Ngerebeg tradition which is carried out at the Kahyangan Kedaton Temple, especially the Kukuh Village community so that the Ngerebeg ceremony remains preserved and is beneficial for the younger generation to understand the deep procession so that it can increase Sraddha and Bhakti to God.